Index of orthodontic treatment needs (IOTN) on orthodontic patients at post graduate orthodontics - Othman, Nurul Amalina; Salim, Jono; Laviana, Avi (Padjadjaran Journal of Dentistry, 2012)
Introduction: Index of Orthodontic Treatment Need (IOTN) was first developed by Brook and Shaw (1989) as a system for grading malocclusions, has 2 components, AC (Aesthetic Component) that shows patient’s subjective needs and DHC (Dental Heath Component) that reveals objective needs for orthodontic treatment. The objective of this research was to know the severity of malocclusion based on IOTN index of orthodontic patients at Post Graduate Orthodontic Clinic Faculty of Dentistry Universitas Padjadjaran from year 2009 to 2010. Method: This descriptive research was done by using data from dental study models of the patients and anterior scale photographs of the patients from the Orthodontic PPDGS students, Faculty of Dentistry Universitas Padjadjaran.  Result: The result of this research shows DHC  59.63% of the patients had definite need for treatment, while 27.52% of the patients had borderline need for treatment and the rest 12.85% of the patients had no need or little need for orthodontic treatment. Meanwhile, according to AC, 49.54% of the patients had no need or little need for treatment, while 33.03% of the patients had definite need for treatment and 17.43% of the patients expressed borderline need for treatment. Conclusion: In a nut shell, by using DHC of IOTN, the highest percentage of patients is in definite need for treatment category. However by using AC of IOTN, the highest percentage of patients is in no need or little need for treatment category.